Exploratory Analysis of Fundamental Spiritual Support Factors to a Positive Attitude in Patients with COVID-19 Using Natural-Language Processing Algorithms - Jorge Sánchez-Garcés; Javier Linkolk López‐Gonzales; Miguel Palacio-Farfán; Víctor Coronel-Sacón; Yonny Ferney-Teheran; Jahisber Peñuela-Pineda; Himer Ávila-George (My University, 2021)
The SARS-CoV-2 virus that causes COVID-19 affects the respiratory tract and is highly infectious. Those patients who knew that the disease could cause death or that their healing process is quite painful because of the symptoms and conditions developed extreme stress, anxiety, and depression, which aggravated the effects of the disease. Therefore, it is vital to conduct research to analyze these effects and generate self-help and support mechanisms during the disease process. This paper presents exploratory analysis related to stress, coping attitudes, emotional responses, and sources of support that were vital in patients affected by COVID-19; the focus of this study is the consideration of the spiritual factor, which may influence religious resilience that allows for a positive attitude and tenacity. To carry out this research, interviews were conducted with patients who had suffered from COVID-19 disease, and the collected information was processed using text-mining techniques using a two-phase methodology. The first phase is based on the Colaizzi method. Interview responses were coded through the search for patterns in the key phrases, and these codes were grouped, forming semantic relationships. In the second phase, natural-language processing algorithms (WordCloud, WordEmbedding, sentiment analysis of opinions) were used, summarizing the interviews in relevant factors of the patient’s experience during the disease. Spiritual resilience stood out the most of all key phrases of the code group tables. Likewise, words such as security, confidence, tranquility, and peace indicated that the patients took a positive attitude towards the symptoms and complications of the disease. Therefore, it is important to be the resilience to face a crisis process, and one of the factors that generated such resilience in COVID-19 patients was religious faith, which was expressed in the interviews using the factors of security, trust, promises of healing, tranquility, and the impossibility of discouragement. All this contributed to the positive attitude of the interviewees during the process of recovery from the disease.
Keywords: Coping (psychology); Anxiety; Psychology; Disease; Exploratory research; Clinical psychology; Social support; Medicine; Applied psychology; Social psychology; Psychiatry; Pathology; Sociology; Anthropology; Coping (psychology); Anxiety; Psychology; Disease; Exploratory research; Clinical psychology; Social support; Medicine; Applied psychology; Social psychology; Psychiatry; Pathology; Social Sciences Psychology Social Psychology Mental Health via Writing; Social Sciences Social Sciences Sociology and Political Science COVID-19 Prevention and Impact; Physical Sciences Computer Science Artificial Intelligence Sentiment Analysis and Opinion Mining